Travel Package Recommendation System - Rohit, M. V.; Manju, Rohan M.; Trishalaa, S.; Ayas, Rashmi B.; Nirmala, J. S. (Journal of Information and Knowledge, 2018)
In the past few years recommender systems have seen an increasing growth and popularity. Despite progress in this area, there are still lots of places to be explored and visited. We first identify and analyze the existing travel packages present in existing system. Major drawback of existing system is that places which have to be seen in the winter season are being considered as a package in the summer season. If a customer wishes to go to some north or northeastern places in winter, they can’t book the package. Our system overcomes this drawback by providing all the places to visit under three categories that is adventure, nature, historic. By this way the customer can choose the type of activity they wish to do and book the places they wish to see.